1996
DOI: 10.1183/09031936.96.09112231
|View full text |Cite
|
Sign up to set email alerts
|

Eosinophils and eosinophil-derived proteins in children with moderate asthma

Abstract: E Eo os si in no op ph hi il ls s a an nd d e eo os si in no op ph hi il l--d de er ri iv ve ed d p pr ro ot te ei in ns s i in n cThe number of eosinophils, serum ECP and EDN, and urinary EDN were determined in 22 children with stable, allergic asthma, aged 4-14 yrs, and in 17 agematched healthy controls. Symptoms were monitored, the peak expiratory flow rate (PEFR) was recorded in the younger children, and lung function tests (forced expiratory volume in one second (FEV1) and the provocative concentration of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
35
1

Year Published

1999
1999
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(37 citation statements)
references
References 20 publications
1
35
1
Order By: Relevance
“…EPX is released by activated eosinophils into the tissue and circulation, and can be detected in urine (8), whereas NO is released by an inducible calcium-independent NO synthase during airway inflammation and can be detected in exhaled air (9). It has been observed that levels of urinary EPX and exhaled NO are higher in asthmatic individuals than healthy control subjects (7,10,11). In addition, close correlations have been seen between levels of eosinophil cationic protein in sputum and both urinary EPX and FeNo (12).…”
mentioning
confidence: 69%
“…EPX is released by activated eosinophils into the tissue and circulation, and can be detected in urine (8), whereas NO is released by an inducible calcium-independent NO synthase during airway inflammation and can be detected in exhaled air (9). It has been observed that levels of urinary EPX and exhaled NO are higher in asthmatic individuals than healthy control subjects (7,10,11). In addition, close correlations have been seen between levels of eosinophil cationic protein in sputum and both urinary EPX and FeNo (12).…”
mentioning
confidence: 69%
“…The number of eosinophils was counted with a Coulter counting chamber. ECP levels were determined as published previously [11]. Briefly, blood was allowed to clot during 1 h after it was drawn.…”
Section: Methodsmentioning
confidence: 99%
“…Elevated uEPX has been reported in asthmatics with or without allergy [3, 4], with great overlap between healthy controls and asthmatics [5, 6]. A relation with asthma symptoms and lung function has been shown, and uEPX increases significantly during asthma exacerbations [79].…”
Section: Introductionmentioning
confidence: 99%